Neurotological Findings at a Health Unit for Adults with Cervicalgia - Zeigelboim,Bianca Simone (2016)
Abstract Introduction The cervical spine is a flexible link between the sensory platform of the skull and torso. The fundamental principle of its operation is due to the balance between muscle strength and flexibility, and any dysfunction of this balance causes neck pain, known as cervicalgia. Objective The objective of this study is to analyze the most prevalent neurotological findings in adults with neck pain. Method A cross-sectional study in which 33 adults from 50 to 83 years of age with neck pain were evaluated and underwent the following procedures: anamnesis, as well as ENT, audiological, and vestibular exams. Results The most evident neurotological symptoms were dizziness (75.7%), tinnitus, neck cracking, tingling in the extremities, and auditory problems (36.3% for each). The most frequently reported clinical symptoms were related to cardiovascular (69.7%), endocrine-metabolic (48.5%), and rheumatic (30.3%) systems. In the audiological assessment, 30 subjects (91.0%) presented hearing impairment in at least one ear, with sensorineural impairment being the most prevalent (88.0%). In the vestibular assessment, there were alterations in 13 subjects (39.0%) found in the caloric test. There was a prevalence of alterations in the peripheral vestibular system with a predominance of irritative peripheral vestibular dysfunction. Conclusion Neurotological complaints were frequent in this population, verifying the importance of these tests in the dysfunctions of the cervical region or the craniocervical junction.